SIM (SISTEM INFORMASI MANAJEMEN) KURIKULUM PERGURUAN TINGGI KEAGAMAAN ISLAM BERBASIS CMS WORDPRESS - Badrudin Badrudin; Rayan Nurdin (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2019)
This study aims to examine Islamic Religious Colleges curriculum information systems based on wordpress CMS. Specifically, this study purposes to explore: 1) the planning of the use of curriculum MIS based on CMS WordPress. 2) the implementation of curriculum MIS which is based on Wordpress CMS, 3) Evaluation of the use of Wordpress CMS-based curriculum MIS. 4) The design concept of the curriculum MIS model based on WordPress CMS. The study used a qualitative approach with a case study of the curriculum Management Information System at the Islamic Education Management (MPI) Study Program of Faculty of Tarbiyah and Teacher Training Islamic University Sunan Gunung Djati (FTIK UIN SGD) Bandung. The subjects of this study were the Chair of the MPI Study Program UIN SGD Bandung, MPI Study Program Information System Operator and the Word CMS application used by the institution. The results of the study show that the MPI Study Program FTIK UIN SGD Bandung used a Curriculum MIS based on Wordpress CMS, and it has succesfully facilitated the students, lecturers, and stakeholders to access the curriculum of study programs easier.